2018
DOI: 10.3389/fmicb.2018.01389
|View full text |Cite
|
Sign up to set email alerts
|

Microbially Mediated Methylation of Arsenic in the Arsenic-Rich Soils and Sediments of Jianghan Plain

Abstract: Almost nothing is known about the activities and diversities of microbial communities involved in As methylation in arsenic-rich shallow and deep sediments; the correlations between As biomethylation and environmental parameters also remain to be elucidated. To address these issues, we collected 9 arsenic-rich soil/sediment samples from the depths of 1, 30, 65, 95, 114, 135, 175, 200, and 223 m in Jianghan Plain, China. We used microcosm assays to determine the As-methylating activities of the microbial commun… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
22
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 36 publications
(23 citation statements)
references
References 80 publications
0
22
0
Order By: Relevance
“…To pinpoint active As methylators, the studies correlated the abundance of arsMharboring microorganisms to the As content in soil or other soil geochemical characteristics. 31,32 The microbial communities in flooded rice paddy soils are distributed in oxic environments, surface soil and rhizosphere, as well as in the bulk, anoxic soil. 33 To date, the isolation of active As methylators from soil has succeeded only for aerobic bacteria 34−36 while, the organisms actively methylating As in anoxic soils remain unknown.…”
Section: ■ Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…To pinpoint active As methylators, the studies correlated the abundance of arsMharboring microorganisms to the As content in soil or other soil geochemical characteristics. 31,32 The microbial communities in flooded rice paddy soils are distributed in oxic environments, surface soil and rhizosphere, as well as in the bulk, anoxic soil. 33 To date, the isolation of active As methylators from soil has succeeded only for aerobic bacteria 34−36 while, the organisms actively methylating As in anoxic soils remain unknown.…”
Section: ■ Introductionmentioning
confidence: 99%
“…Efforts to identify the key microbial mediators of As methylation have involved metagenomic as well as gene amplification approaches. These studies have shown that the phylogenetic diversity of arsM genes from paddy soil microbial communities is extensive. To pinpoint active As methylators, the studies correlated the abundance of arsM -harboring microorganisms to the As content in soil or other soil geochemical characteristics. , The microbial communities in flooded rice paddy soils are distributed in oxic environments, surface soil and rhizosphere, as well as in the bulk, anoxic soil . To date, the isolation of active As methylators from soil has succeeded only for aerobic bacteria while, the organisms actively methylating As in anoxic soils remain unknown.…”
Section: Introductionmentioning
confidence: 99%
“…Having described the key role of Shewanella species in the facilitation of direct or indirect mobilisation of environmental As species, its potential remediation role could be best perceived from its contribution to the detoxification of some As species and/or sequestration of the mobilised As through flavin-mediated iron plaque formation [104][105][106]. These various processes are explained in detail in the upcoming sections of this article.…”
Section: Mitigation and Remediation Strategies For Arsenicmentioning
confidence: 99%
“…Additionally, the bacteria involved have the potential to dramatically alter the geochemistry of the surrounding Fe mineral-containing As in groundwater and sediments, resulting in As contamination of drinking water sources, diseases, poisoning, and human health disruption [39,133,134]. Numerous bacterial strains were identified to be involved in the reduction and transformation of Fe, particularly in the As(V)-bearing Fe(III) mineral assemblage [104,135,136]. These bacteria include dissimilatory iron-reducing bacteria (DIRB) and dissimilatory arsenic-reducing bacteria (DARB), comprising Shewanella oneidensis MR-1 and Geobacter metallireducens GS-15 and Geobacter sp.…”
Section: Effect Of Dissimilatory Iron-reducing Bacteria's Transformat...mentioning
confidence: 99%
See 1 more Smart Citation